INFANT BACTERIAL MENINGITIS: DIAGNOSTIC, THERAPEUTIC, AND PROGNOSTIC CHALLENGES IN RECENT CASE REPORTS (International Seven Journal of Health Research, 2026)
Introduction: Pediatric bacterial meningitis is a rapidly progressive medical emergency with high morbidity and mortality, especially in neonates and young infants, due to immunological immaturity and the wide diversity of etiological agents. Despite advances in vaccination, the disease remains a major global public health challenge.Methods: This systematic review analyzed 20 case reports published over the last five years, selected from the PubMed, Medline, and LILACS databases. The descriptors “Meningitis, Bacterial,” “Pediatrics,” and “Clinical Diagnosis” were used. Of the 118 articles initially identified, after screening titles, abstracts, and full texts, 20 case reports met the inclusion criteria.Results: Fourteen distinct agents were identified, with predominance of Streptococcus pneumoniae (20%) and Streptococcus agalactiae (10%). Listeria monocytogenes and Mycoplasma hominis also accounted for 10% each. Children under 12 months of age represented nearly 50% of cases. The most frequent clinical manifestations were fever (85%), seizures (35%), vomiting (30%), and irritability (20%), while classic meningeal signs were present in only 20% of patients. The most commonly used empirical treatment was a combination of a third-generation cephalosporin and vancomycin, with therapeutic adjustment required in 70% of cases after culture and antibiogram. Eleven children recovered without sequelae, while nine developed neurological deficits, such as hearing loss, residual hydrocephalus, motor deficits, and cranial neuropathies, and one death was associated with non-K1 Escherichia coli.Conclusion: Pediatric bacterial meningitis shows marked etiological heterogeneity and clinical variation according to age group, hindering early diagnosis, particularly in neonates. Although appropriate treatment favors good outcomes, more virulent or resistant pathogens remain associated with significant neurological complications and mortality. Immediate initiation of empirical antibiotic therapy, followed by adjustment according to the isolated agent, is essential for a better prognosis. The expansion of vaccination coverage against S. pneumoniae, Haemophilus influenzae type b, and meningococcus is also emphasized as a fundamental measure for prevention and reduction of morbidity and mortality.